Penerapan Pendidikan Lingkungan Hidup Di Perguruan Tinggi Dengan Model Outdoor Learning - Ali, Muhammad; Ardi, Muhammad; Tahmir, Suradi (UNM Environmental Journals, 2018)
environmental learning aims that students have concern for the surrounding environment. The learning model of environmental learning (EL) described in this article applies the outdoor learning method. Learning materials presented to students are arranged by involving the surrounding environment. This means that learning can be done not only in classrooms, but also outside the classroom in order for students to be more comfortable and active in the learning process. the initial ability of students needs to be considered in the learning process because it affects the ability of students to follow the next learning process. This article describes the meaning, goals and benefits, advantages and disadvantages and the stages of the method of outdoor learning. So that it can be concluded that higher education is education in higher education that has several general goals / principles where knowledge (knowledge) is created, used continuously and a place of search for knowledge, solving various problems, where to criticize the works produced, or as the place for the formation and development of student character to become a student who has high reasoning, sharp and broad analysis. Especially in environment-based learning developed so that students gain more experience related to the surrounding environment.